Vaccine Development Against Tuberculosis Over the Last 140 Years: Failure as Part of Success - Kaufmann, Stefan H. E. (Frontiers in Microbiology, 2021)
The year 2020 is shaped by the Covid-19 pandemic which has killed more people than any other infectious disease in this particular year. At the same time, the development of highly efficacious vaccines within less than a year raises hope that this threat can be tamed in the near future. For the last 200 years, the agent of tuberculosis (TB) has been the biggest killer amongst all pathogens. Although a vaccine has been available for 100 years, TB remains a substantial threat. The TB vaccine, Bacille Calmette-Guérin (BCG), has saved tens of millions of lives since its deployment. It was the best and only choice available amongst many attempts to develop efficacious vaccines and all competitors, be they subunit vaccines, viable vaccines or killed whole cell vaccines had failed. Yet, BCG is insufficient. The last decades have witnessed a reawakening of novel vaccine approaches based on deeper insights into immunity underlying TB and BCG immunization. In addition, technical advances in molecular genetics and in the design of viral vectors and adjuvants have facilitated TB vaccine development. This treatise portraits early developments of TB vaccines leading to BCG as the sole preventive measure which stood the test of time, but failed to significantly contribute to TB control. Then more recent attempts to develop novel vaccines are described with the focus on the genetically modified BCG-based vaccine, VPM1002, which has become the frontrunner amongst viable TB vaccine candidates. It is hoped that highly efficacious vaccines against TB will become available even though it remains unclear whether and when this ambition can be accomplished. In any case, it is clear that the goal of reducing TB morbidity and mortality by 90 or 95%, respectively, by 2030 as proposed by the World Health Organization, strongly depends on better vaccines.